Nanoencapsulation of Antitumor and Antituberculosis Drug Preparations with Biocompatible Polymers - Burkeev, M. Zh.; Kreuter, J.; Herk, A. Van; Tazhbayev, Y. M.; Zhaparova, L. Zh.; Zhumagalieva, T. S.; Zhappar, N. K. (Journal of Research Updates in Polymer Science, 2014)
Controlled release of drugs at the locus of the targeted disease is one of the most challenging research areas in the pharmaceutical field. Nowadays novel drug delivery systems on the basis of polymers are attracting great attention since they can improve therapeutic efficiency of potent drug preparations decreasing the risk of side effects. By developing colloidal drug delivery systems such as liposomes/vesicles and polymeric nanoparticles and nanocapsules the pharmacokinetics of the drug can be changed and thus the therapeutic efficiency of the drug can be increased. Nanoparticles with their special characteristics such as small particle size, large surface area and high capacity of carrying biologically active substances offer a number of advantages compared to other colloidal drug delivery systems [1, 2]. Controlled drug release systems are constructed on the basis of natural and biocompatible synthetic polymers. Among the most promising biocompatible polymers human serum albumin (HSA), polyalkyl cyanoacrylates (PACA) and poly-D,L-lactic acid (PLA) are of great importance. Nanoparticles on their basis have been proven to be efficient in treatment of serious and long-termed diseases such as tumors, tuberculosis and bacterial infections [3-126]. Therefore this article is aimed to give a brief review on the research works devoted to the synthesis and investigation of polymeric nanoparticles and nanocapsules based on PACA, HSA and PLA for the past three decades.